Post-Conflict Economies in Africa - Fosu, A (Palgrave Macmillan, 2005)
Thirteen papers, originally presented at an African Economic Research Consortium Special Workshop in Kampala in July 2002, explore issues relating to postconflict economics and include case studies drawn from all regions of sub-Saharan Africa. Papers discuss the postconflict reconstruction in Africa; the economic and political consequences of conflict and implications for postconflict recovery in Africa; economic policy in postconflict societies; ethnicity, institutions of governance, and conflict avoidance; Liberia and Sierra Leone; the Nigerian Civil War; the economics of civil conflict in Africa and the case of Chad; conflict, postconflict, and economic performance in Ethiopia; prospects for sustainable peace and postconflict economic growth in the Sudan; the challenge of entrenching peace in postconflict economies and the case of Uganda; the challenge of transition from war to peace in Burundi; the political economy of postconfict economic recovery; transformation for postconflict Angola; and postconflict economies in Africa. Fosu is with the Economic Commission for Africa. Collier is at Oxford University. Name and subject indexes.